First-in-patient study of OTL78 for intraoperative fluorescence imaging of prostate-specific membrane antigen-positive prostate cancer: a single-arm, phase 2a, feasibility trial - Stibbe, Judith A; de Barros, Hilda A; Linders, Daan G J; Bhairosingh, Shadhvi S; Bekers, Elise M; van Leeuwen, Pim J; Low, Philip S; Kularatne, Sumith A; Vahrmeijer, Alexander L; Burggraaf, Jacobus; van der Poel, Henk G (The lancet oncology, 2023)
Targeted real-time imaging during robot-assisted radical prostatectomy provides information on the localisation and extent of prostate cancer. We assessed the safety and feasibility of the prostate-specific membrane antigen (PSMA)-targeted fluorescent tracer OTL78 in patients with prostate cancer. In this single-arm, phase 2a, feasibility trial with an adaptive design was carried out in The Netherlands Cancer Institute, Netherlands. Male patients aged 18 years or older, with PSMA PET-avid prostate cancer with an International Society of Urological Pathology (ISUP) grade group of 2 or more, who were scheduled to undergo robot-assisted radical prostatectomy with or without extended pelvic lymph node dissection were eligible. All patients had a robot-assisted radical prostatectomy using OTL78. Based on timing and dose, patients received a single intravenous infusion of OTL78 (0·06 mg/kg 1–2 h before surgery [dose cohort 1], 0·03 mg/kg 1–2 h before surgery [dose cohort 2], or 0·03 mg/kg 24 h before surgery [dose cohort 3]). The primary outcomes, assessed in all enrolled patients, were safety and pharmacokinetics of OTL78. This study is completed and is registered in the European Trial Database, 2019-002393-31, and the International Clinical Trials Registry Platform, NL8552, and is completed. Between June 29, 2020, and April 1, 2021, 19 patients were screened for eligibility, 18 of whom were enrolled. The median age was 69 years (IQR 64–70) and median prostate-specific antigen concentration was 15 ng/mL (IQR 9·3–22·0). In 16 (89%) of 18 patients, robot-assisted radical prostatectomy was accompanied by an extended pelvic lymph node dissection. Three serious adverse events occurred in one (6%) patient: an infected lymphocele, a urosepsis, and an intraperitoneal haemorrhage. These adverse events were considered unrelated to the administration of OTL78 or intraoperative fluorescence imaging. No patient died, required a dose reduction, or required discontinuation due to drug-related toxicity. The dose-normalised maximum serum concentration (Cmax/dose) in patients was 84·1 ng/mL/mg for the 0·03 mg/kg dose and 79·6 ng/mL/mg for the 0·06 mg/kg dose, the half-life was 5·1 h for the 0·03 mg/kg dose and 4·7 h for the 0·06 mg/kg dose, the volume of distribution was 22·9 L for the 0·03 mg/kg dose and 19·5 L for the 0·06 mg/kg dose, and the clearance was 3·1 L/h for the 0·03 mg/kg dose and 3·0 L/h for the 0·06 mg/kg dose. This first-in-patient study showed that OTL78 was well tolerated and had the potential to improve prostate cancer detection. Optimal dosing was 0·03 mg/kg, 24 h preoperatively. PSMA-directed fluorescence imaging allowed real-time identification of visually occult prostate cancer and might help to achieve complete oncological resections. On Target Laboratories.